Design a better business new tools, skills, and mindset for strategy and innovation - Pijl, Patrick van der; Lokitz, Justin; Solomon, Lisa Kay (Ascent Audio, 2024)
This book stitches together a complete design journey from beginning to end, guiding listeners (you) step-by-step in a practical way from the initial spark of an idea all the way to scaling it into a better business. Design a Better Business includes a comprehensive set of tools (over twenty total!) and skills that will help you harness opportunity from uncertainty by building the right team(s) and balancing your point of view against new findings from the outside world. This book also features over fifty case studies and real life examples from large corporations such as ING Bank, Audi, Autodesk, and Toyota Financial Services, to small startups, incubators, and social impact organizations, providing a behind the scenes look at the best practices and pitfalls to avoid. Also included are personal insights from thought leaders such as Steve Blank on innovation, Alex Osterwalder on business models, Nancy Duarte on storytelling, and Rob Fitzpatrick on questioning, among others.